Necrobiosis Lipoidica Diabeticorum - Kanchan Pramila; Jayanth D P; Shenoi S D; Sandra A (Wolters Kluwer Medknow Publications, 2001)
We present a case of necrobiosis lipoidica in a 55 year old female diabetic patient with multiple, disseminated lesions on both the legs, forearms, truck,, buttocks and face.